Patterns of Maltreatment Co-Occurrence in Incarcerated Youth in Australia - Papalia, Nina (Journal of interpersonal violence, 2022)
Child maltreatment research is increasingly recognizing the need to capture patterns of co-occurrence between different types of abuse/neglect and to consider their associations with psychosocial functioning. Few studies have examined these issues in justice-involved youth despite the fact that rates of maltreatment and trauma-related psychopathology are disproportionately high among this population. This study examined profiles of self-reported child physical abuse, sexual abuse, emotional abuse, and neglect among incarcerated juveniles in Victoria, Australia, using latent class analysis. We also investigated associations between maltreatment profiles and mental health and behavioral problems. Data pertaining to juveniles? experiences of maltreatment and mental health and behavioral functioning were collected from interviews, questionnaires, files, and administrative datasets. A three-class solution provided the best fit for the data and was conceptually meaningful: a ?low/rare maltreatment? class (41%); ?high physical and emotional abuse? class (23%); and a ?poly-victimization? class (36%). Youth in the ?poly-victimization? class experienced especially serious mental health and behavioral disturbances, including higher rates of mental illness, greater severity of internalizing and externalizing symptoms, impulsivity, substance abuse, self-harm and suicidal behavior, irritability, and early-onset violence. Results suggest there may be benefit in considering screening and assessment procedures in youth justice settings to identify poly-victimized youth in need of more intensive monitoring and treatment to address their complex clinical and behavioral profiles.